PENERAPAN SUNNAH-SUNNAH WUDHU BERDASARKAN KITAB HADIS BULUGHUL MARAM BAB THOHARAH ( STUDI KASUS SANTRI PONDOK PESANTREN MAWARIDUSSALAM ) KEC. BATANG KUIS, KAB. DELI SERDANG - Sulaiman Muhammad Amir; Munandar Munandar; Taufik Romadhon Dalimunthe (SHAHIH (Jurnal Ilmu Kewahyuan), 2021)
Wudhu is an obligatory condition for performing the five daily prayers. So if you don't perform ablution, your prayer is invalid. Educators at Islamic boarding schools certainly play a major role in educating and teaching their students to perform ablution properly and correctly both in harmony and in the sunnah. This study aims to 1. Determine the process of applying the sunnah of ablution according to the book of Bulughul Maram chapter of ablution in the students of the Mawaridussalam Islamic Boarding School. 2. To find out the results of the application of the sunnah of ablution on the students of the Mawaridussalam Islamic Boarding School. This research was carried out by means of a qualitative approach. The subjects of this study were students and teachers of hadith subjects at Mawaridussalam Islamic Boarding School. The object of this research is the application of the sunnah of ablution in the book Bulughul Maram which is applied to the students of the Mawaridussalam Islamic Boarding School. The technique used in determining the subject of this study uses a purposive technique, namely the technique of determining informants with certain considerations. Data collection techniques by conducting in-depth interviews, participatory observation and documentation. The results of this study indicate that the learning process and the implementation of the sunnah-sunnah ablution for the students of the Mawaridussalam Islamic Boarding School, especially in the third grade (3B) are quite good. As in learning activities the teacher uses a variety of interesting methods so that students are enthusiastic in participating in class. Teachers also carry out field control or monitoring activities to determine the implementation of students in the field.